Free-caged rearing modes regulate chicken intestinal metabolism by influencing gut microbial homeostasis - Tao Li; Peng Wang; Zhuo Zhi; Tong Guo; Jie Zhou; Huiya Zhang; Chang Cao; Yingjie Cai; Yuxiao Li; Jianqin Zhang (Poultry Science)
Free-caged rearing modes, which prioritize animal welfare, are believed to enhance the quality of animal products. The impact of rearing modes on meat quality may play a key role in the superior quality of local chicken breeds. This study analyzed the cecal contents of free-range and caged black-bone chickens at different ages using metagenomic and metabolomic sequencing. We identified 32 metabolites and 367 microbial species significantly affected by the rearing mode. Linear discriminant analysis Effect Size (LefSe) highlighted five key microorganisms, Gemmiger formicilis, Bacteria unclassified, Bacteroides sp. ET225, Massilistercora timonensis, and Bacteroidales unclassified, that showed distinct abundance patterns across all age points. Among them, Bacteroides sp. ET225 and Massilistercora timonensis were positively associated with certain phospholipids and plant-derived metabolites, while negatively correlated with others like demissidine and acylcarnitine. Functional analysis revealed that rearing modes impact gut metabolites involved in gut metabolism as well as broader processes such as signal transduction, protein digestion, and autophagy. This study offers new insights into how rearing modes influence gut microbiota and metabolites, shedding light on the study of rearing mode-mediated muscle development and fat deposition.